Trapezius Motor Evoked Potentials From Transcranial Electrical Stimulation and Transcranial Magnetic Stimulation: Reference Data, Characteristic Differences and Intradural Motor Velocities in Horses - Journée, Sanne Lotte; Journée, Henricus Louis; Berends, Hanneke Irene; Reed, Steven Michael; Bergmann, Wilhelmina; de Bruijn, Cornelis Marinus; Delesalle, Cathérine John Ghislaine (Frontiers in Neuroscience, 2022)
Abstract Reason for performing study: So far, only transcranial muscle evoked potentials (MEP) of the extensor carpi radialis and tibialis cranialis have been documented for diagnostic evaluation in horses. These allow for differentiating whether lesions are located in either the thoraco-lumbar region or in the cervical myelum and/or brain. Transcranial trapezius MEPs enable to further distinguish between spinal and supraspinal located lesions. No normative data are available. It is unclear whether TES (transcranial electrical) and TMS (transcranial magnetic stimulation) are interchangeable modalities. Objectives: To provide normative data for trapezius MEP parameters in horses for TES and TMS, to discern direct and indirect conduction routes by neurophysiological models that use anatomical geometric characteristics to relate latency times with peripheral (PV) and central conduction velocities (CV). Methods: TES-induced trapezius MEPs were obtained from twelve horses. TES and TMS MEPs (subgroup 5 horses) were compared intra-individually. Trapezius MEPs were measured bilaterally twice at 5 intensity steps. Motoneurons were localized using nerve conduction models of the cervical and spinal accessory (SAN) nerves. Predicted CVs were verified by multifidus MEP data from two horses referred for neurophysiological assessment. Results: MEP latencies for TES: ELmean=13.5 (11.1-16.0)ms and TMS: MLmean=19.7 (12-29.5)ms. EL’s comprise ~100% direct routes. MLmean revealed mixed direct/indirect routes of L:23/50; R:14/50. Left/right latency decreases over stimulation intensity increases EL10>50V :-1.4 /-1.8ms and ML10>50% :-1.7/-3.5ms. Direct route ML-EL differences were 1.88 - 4.30ms. Maximum CVs: 180m/s. 95% MEP amplitudes ranges for TES: L:0.26–22mV; R:0.5–15mV and TMS L:0.9 – 9.1mV; R:1.1– 7.9mV. Conclusions: This is the first study to report normative data characterizing TES and TMS induced- trapezius MEPs in horses. The complex trapezius innervation leaves TES as only reliable stimulation modality. Differences in latency times along the SAN route permit to estimate the location of active motoneurons, which is of importance for clinical diagnostic purpose. SAN route lengths and latency times are governed by anatomical locations of motoneurons across C2-C5 segments. TES intensity dependent reductions of trapezius MEP latencies are similar to limb muscles while MEP amplitudes between sides and between TES and TMS are not different. CVs may reach 180m/s.